علاقة بيئة العمل بالرضا الوظيفي للعمال - أهناني، نجاح (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة باللغة العربية تعالج هذه الدراسة علاقة بيئة العمل بالرضا الوظيفي للعمال, حيث اعتمدنا في اشكاليتنا على التساؤل التالي: هل توجد علاقة بين بيئة العمل والرضا الوظيفي للعمال معمل التمور؟ وتندرج تحت هذا التساؤل الرئيسي الأسئمة التالية: _ هل توجد علاقة بين الظروف الفيزيقية والرضا الوظيفي للعمال؟ _ هل توجد علاقة بين علاقات العمل والرضا الوظيفي للعمال؟ _ هل توجد علاقة بين طبيعة العمل والرضا الوظيفي للعمال؟ وقد تم صياغة الفرضية العامة للدراسة على أن بيئة العمل لها علاقة بالرضا الوظيفي لمعمال, ويندرج تحت هذا الفرضية ثلاث فرضيات جزئية: الظروف الفيزيقية لها علاقة بالرضا الوظيفي, وعلاقات العمل لها علاقة بالرضا الوظيفي, وطبيعة العمل لها علاقة بالرضا الوظيفي. ولمتابعة الدراسة قمنا بالاعتماد على المنهج الوصفي, حيث اعتمدنا مسح شامل للأفراد المتمثلين في عمال معمل التمور في بمدية سيدي عمران, حيث تضمنت الاستمارة تسعة وعشرون سؤالا, مقسمة الى ثلاثة محاور هي: محور البيانات الأولية ومحور بيئة العمل ومحور الرضا الوظيفي, وحسب النتائج المتحصل عليها تبين تحقق الفرضيات الموضوعة سالفا.Study Summary In English This study deals with the relationship of the work environment to satisfaction of the workers. In out preblomatic, we relied on the following question: Is there a relationship between the work environment and job satisfaction of workers in the date lab? *Under this main question (preblomatic), the following questions atise: Is there a relationship between physical conditions and job satisfaction of workers ? Is there a relationship between labor relations and job satisfaction for workers ? Is there a relationship between the nature of work and job satisfaction of workers? The general premise of the study is that the work environment is related to the job satisfaction of the workers. Under this hypothesis, fall three hypotheses: Physical conditions have to do with job satisfaction, and work relations to job satisfaction, and the nature of work related to job satisfaction. In order to continue the study, we relied on the descriptive approach. We adopted a comprehensive survey of the personal represented in the date lab workers in the municipality of Sidi Amran. The questionnaire included twenty-nine questions divided into three axes: the primary data axis, the focus of the work environment and , the focus of the job satisfaction and according to the results obtained, the above hypothesis are validate.
دراسة ميدانية على عمال شركة صابيودات لتصدير التمور ببلدية سيدي عمران
مذكرة ماستر علوم إجتماعية تخصص تنظيم وعمل
Keywords: الرضا الوظيفي، بيئة العمل; Satisfaction au travail, environnement de travail; Job satisfaction, work environment